2014
DOI: 10.3892/or.2014.3319
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1290 promotes asiatic acid-induced apoptosis by decreasing BCL2 protein level in A549 non-small cell lung carcinoma cells

Abstract: Asiatic acid, a triterpenoid derived from Centella asiatica, is a putative anticancer agent in several types of cancer cells. Investigations of its biological role in negative regulation of cell growth have focused on the extent of induction of apoptosis in a cell-type-specific manner. In this study, we identified an important regulator of asiatic acid-induced cell death, microRNA (miR)-1290, which sensitizes cells to asiatic acid-induced cytotoxicity and negatively regulates BCL2 expression. Asiatic acid sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…In this work, we found AA could promote cardiomyocyte survival under hypoxic conditions by up regulating the level of miR‐1290. A research by Kim et al investigated the effect of AA treatment of A549 cells on miRNA expression profiles using miRNA microarray analysis and found miR‐1290 were significantly increased by 44.56 fold. Although they did not examine whether AA increases transcription of miR‐1290 or enhances its stability, they speculated this increase may be mediated at the transcriptional level .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we found AA could promote cardiomyocyte survival under hypoxic conditions by up regulating the level of miR‐1290. A research by Kim et al investigated the effect of AA treatment of A549 cells on miRNA expression profiles using miRNA microarray analysis and found miR‐1290 were significantly increased by 44.56 fold. Although they did not examine whether AA increases transcription of miR‐1290 or enhances its stability, they speculated this increase may be mediated at the transcriptional level .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Huang et al suggested AA could protect rat H9c2 cardiomyocytes against oxygen‐glucose deprivation/reoxygenation induced apoptosis partly via the Akt/GSK‐3β/HIF‐1α pathway. Kim et al investigated the effect of AA treatment on the miRNA expression profiles of human non‐small cell lung cancer A549 cells and found miR‐1290 was significantly increased by 44.56 fold, suggesting AA may play its biologic role through regulating miR‐1290. Bioinformatic analyses (TargetScan and RNA22) suggest that HIF3A is a potential target gene of miR‐1290.…”
Section: Introductionmentioning
confidence: 99%
“…An et al reported that miR-1290 is increased in A549 cells treated with ginsenoside Rh2 [18]. Furthermore, Kim et al found that miR-1290 was increased in A549 cells when treated with asiatic acid and promoted cell apoptosis by decreasing Bcl-2 expression [19]. However, the expression and function of miR-1290 in CSLCs of NSCLC are poorly characterized.…”
Section: Discussionmentioning
confidence: 96%
“…1b, miR-1290 was significantly increased in CD133 + cells compared with NSCLC cells by real-time PCR, which has been widely explored in multiple cancers, such as pancreatic and colon cancer [16,17]. However, there are few reports about effects of miR-1290 on NSCLC [18,19], especially in CSLCs. Therefore, the role of miR-1290 in tumorigenesis was investigated in the following study.…”
Section: Mir-1290 Was Increased In Cd133 + Cellsmentioning
confidence: 94%
“…Reduction up to 50% in viability was observed in ovarian cancer cells treated with 40 ug/ml concentration of asiatic acid, and it also showed cell cycle arrest at the G0/G1 phase and increased apoptosis by 7-10 folds [24]. Induction of apoptosis was observed in A-549 cell line due to presence of asiatic acid which helped in regulation of miR-1290, BCL2 protein level, and cell cycle regulation [25].…”
Section: Prakash Et Almentioning
confidence: 89%